Second-Generation Azafullerene Monoadducts as Electron Acceptors in Bulk Heterojunction Solar Cells - Bothe, Michael; Montero-Rama, María Pilar; Viterisi, Aurélien; Cambarau, Werther; Stenta, Caterina; Palomares, Emilio; Marsal, Lluis F.; von Delius, Max (Synthesis, 2018)
Four new azafullerene monoadducts (DPS-C59N, HDP-C59N, DBOP-C59N, DHOP-C59N) have been prepared and applied as electron acceptors in solution-processed bulk heterojunction solar cells. The four compounds were designed so that their solubility in organic solvents was maximized and that structure–property comparisons could be drawn with a previously synthesized azafullerene electron acceptor. With the photovoltaic devices that were prepared from the four azafullerenes and polymeric electron donor PTB7 we found that only one of the four new electron acceptors resulted in a power conversion efficiency that exceeded the one observed with a previously reported azafullerene monoadduct. Atomic force microscopy and electron mobility measurements suggest that azafullerenes bearing two alkyl chains lead to non-optimal film morphologies as well as electron mobilities and that future efforts should focus on single n-alkyl substitution.
Keywords: fullerenes; azafullerenes; electrophilic aromatic substitution; organic photovoltaics; structure-property relationships